Analisis Deskriptif Representasi Kata “Hujan” Dalam Novel Hujan Karya Tere Liye - Bagus Satrio, Moh. Nurman (MAN Insan Cendekia Jambi, 2025)
The novel “Hujan” by Tere Liye is a literary work that combines elements of science fiction with the theme of love and struggle. The story is set between 2042 and 2050, where the world experiences a terrible natural disaster due to a volcanic eruption that results in a depopulation of the human population. The main character, Lail, is a girl who loses both of her parents due to the disaster and meets Esok, a young man who saves her. The purpose of this study is to analyze the word rain in Tere Liye's novel Hujan. The author uses a qualitative method with the data used being the novel Hujan by Tere Liye. In this novel, the word hujan is not just a natural phenomenon, but a symbol rich in meaning and emotion. In this novel, hujan functions to describe various themes such as loss, love, friendship, and the main character's life struggles. Hujan has a deep representation both in terms of physicality and mood. Physically, rain describes extreme climate change due to natural disasters, such as an ancient volcanic eruption that causes a volcanic winter. Rain reflects the emotions and journeys of the main characters, Lail and Esok. Rain is often associated with feelings of sadness, loss, and hope. The representation of rain in this novel not only functions as a physical element, but also as a tool to describe the emotional dynamics between characters and criticism of the environmental conditions faced by humanity.